Development of Cartoon Puppet Media to Improve Understanding of Sexual Education in Elementary School Students - Andi Wijayanto; Muhammad Nur Wangid (AL-ISHLAH: Jurnal Pendidikan, 2024)
Sexual education is still considered sensitive to discuss with elementary school children. This makes children have a low understanding of sexual education information. This condition is exacerbated by the absence of media to provide sexual education to students, so this study aims to develop cartoon puppets in puppet plays about sexual education for grade VI SD X students. This research is research and development that adopts the Borg and Gall research design. The test subjects in this research were material experts and media experts. Based on the results of research from these experts, cartoon puppet media in puppet plays about sexual education for sixth grade elementary school students is very good/suitable for use with an average score of 78.75% from the material expert assessment and 80% from the media expert assessment. Based on the test results, the score percentage is 82%, thus the product that has been tested is included in the very good category. The results of this development research can be used by guidance and counseling teachers or class teachers to provide an understanding of sexual education to elementary school students.